Design and fabrication of environmental noise reduction device - Qamaruddin, Mohd Fauzi (2012)
This project is about designing and fabricating the environmental noise reduction device to help people while doing their work in gas turbine laboratory. This project involves the process of designing the device using the considering reduction rate and ergonomic factor for laboratory used. After the design has complete, it was transformed to its real product where the design is used for guideline. These project also require ensuring the safety for indeed of publishing. Method and process involve in this project for instance joining using bending, welding, drilling and cutting process. This project is mainly about generating a new concept of environmental noise reduction device that could minimize the noise around laboratory that helps to give convenience workplace to others. After all process had been done, this noise reduction device may help us to understand the fabrication and designing process that involve in this project. This product is tested with place it to Gas Turbine Machine at FKM laboratory. As the result, the sound rate is reducing into 73.5 dB which is reducing 35% before the product is placed. Through this testing show that product fulfills the objective to make an ergonomic product to human hearing